Green spaces in Ghana’s built environment: Analyzing perceptions and urban planning perspectives through the lens of the New Environmental Paradigm - Lukman Kura Abraham Safo; Abdul- Rafiw Safo; Stephen Biliyitorb Liwur; Emmanuel Kwame Nti (City and Environment Interactions)
In the busy world of city growth, urban green spaces in Ghana are befallen with destruction due to urbanization. Using a cross-sectional design and case-studying Damongo and Kintampo, this study assessed the perceptions of urban residents and urban planning perspectives about green spaces in enhancing the environmental condition of fast-growing urban areas, and proposed guidelines for the managing green spaces within Ghana’s built environment. The results revealed that underutilization and insufficient funding for greenspace management increase vulnerability to urban encroachment, especially during inward city growth. Again, the exhaustion of the limited resources of the earth could have repercussions for the population of the earth; however, the need for such resources and the level of poverty influences poor environmental decisions. Further, the results showed that planning for urban green and open space ought to be decided at the local level. The study, therefore, recommends a collaborative approach involving city authorities, private sectors, and the public for effective green space management, emphasizing inclusive decision-making and active preservation, and the development of local standards within a national framework, guided by an urban green spaces protection scheme.